Reclamation in southern China: The early Chu’s agriculture revealed by macro-plant remains from the Wanfunao site (ca. 1000–770 BCE) - Yang, Ruichen; Tang, Liya; Zhao, Dong; Huang, Wenxin; Luo, Yunbing (Frontiers in Plant Science, 2022)
The Wanfunao site was a large Chu settlement in Zhou Dynasty, which lay in an alluvial plain along the Yangtze River in the Yichang section. The region of the site is a type of compatible environment within mountains, hills, and plains. Previous studies have suggested that the middle and lower reaches of the Yangtze River are one of the best regions for rice cultivation. Besides rice, however, there are 7 dryland crops found at the Wanfunao site: foxtail millet, broomcorn millet, wheat, barley, oat, buckwheat, and adzuki bean. Among them, the ubiquity of foxtail millet and rice is extraordinary. The crop assemblage of the site has revealed that the northern dryland crops gradually dispersed southward and became a part of the diet besides rice. This inevitable consequence can be attributed to southerners' reclamation for agriculture. Although southern ancestors developed rice cultivation in the plains, hilly and mountainous areas provided a “buffer zone” which allowed northern dryland crops to grow in the southern regions. Meanwhile, with deeper human cognition of agriculture and the adaptation to the seasonality changes for northern plants, the multi-crop farming system was gradually promoted in southern China. Additionally, the assemblage of “foxtail millet grain/rice spikelet base” in the site may be involved in livestock feeding. Likely, a wide range of landforms, compatible farming, and surplus agricultural products for husbandry may be the close companions to the gradual development and prosperity of the early Chu.